Research on formulation optimization and hydration mechanism of phosphogypsum-based filling cementitious materials - Yang, Xiao; Jia, Yongxiang; Yang, Chen; He, Xiaoke; Jia, Yanchang; Xu, Leige (Frontiers in Environmental Science, 2022)
Phosphogypsum is a solid waste produced in the production of wet-process phosphoric acid. The main component is calcium sulfate dihydrate, and its constant calcium activity is very low. It is a very difficult waste to handle. The slag produced in the ironmaking processes of the Jiuquan Iron and Steel Company has high activity and can be mixed with phosphogypsum to prepare backfilling cementitious materials for the backfilling of goaf (see Introduction below) to prevent its subsidence and cracking and subsequent subsidence of the land surface above the goaf. In this paper, an orthogonal test of material strength under different ratios and finenesses was carried out, and the optimal formula of phosphogypsum-based cementitious material was obtained. On this basis, SEM (Scanning Electron Microscope) and XRD (X-ray Diffraction) were used to observe the internal structure of phosphogypsum-based cementitious materials. The results show that: when the content of quicklime is 5.5%–6.0%, the content of phosphogypsum is 30%–33%, the content of NaOH is 1.5%–2.0%, the content of Glauber’s salt is 2.5%–3%, the average particle size is 15.88 μm, and grinding aids and an early strengthening agent were added, and in the case of the strengthening agent, the 3-days and 7-days strengths of the filling reached the highest values of 1.58 MPa (mean flexural strength) and 4.1 MPa, respectively. The formation of calcium silicate hydrates gel (C-S-H) and ettringite (AFt) gradually increased with age, and the structure became denser. The ettringite plays the role of interspersed support in the filling body, thereby improving the overall strength. This research provides a theoretical basis and practical reference for the treatment of goaf.